Novel coronavirus infection and children - Cavallo, Federica; Rossi, Nadia; Chiarelli, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Its outbreak in many states of the world, forced the World Health Organization (WHO) to declare a pandemic. Currently, COVID-19 has infected 1 991 562 patients causing 130 885 deaths globally as of 16 April 2020. The aim of this review is to underline the epidemiological, clinical and management characteristics in children affected by COVID-19. Methods: We searched Pubmed, from January to April 2020, for the following search terms: “COVID-19”, “children”, “SARS-COV2”, “complications”, “epidemiology”, “clinical features”, focusing our attention mostly on epidemiology and symptoms of COVID-19 in children. Results: Usually, infants and children present milder symptoms of the disease with a better outcome than adults. Consequently, children may be considered an infection reservoir that may play a role as spreader of the infection in community.